Say cheese and die-- again! - Stine, R. L. (New York : Scholastic, 1996)
Bad things happen when Greg determines to convince his English teacher of the powers of the evil camera.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
440
Accelerated Reader AR
Keywords: Cameras -- Juvenile fiction; Photography -- Juvenile fiction; Horror tales; Horror fiction